MOTIVASI BERPRESTASI, DUKUNGAN SOSIAL DAN FLOW AKADEMIK SISWA DI ERA COVID-19 - Elsa Kristanti; Nila Puspita Sari (Bajang Institute, 2021)
Academic flow during the pandemic is much needed in supporting learning activity primarily in online learning process. This study aims at identifying the effect of achievement motivation and social support toward Senior High School students’ academic flow in Kefamenanu, East Nusa Tenggara. This research involved 191 samples through probability technique especially simple random sampling, while multiple regression technique was used in analyzing data. Based on data analysis for t test, it showed that tcount value of achievement was 4.215 > ttable (1.972) with a significant value 0.000 < 0.05, tcount value of social support was about 2.515 > ttable (1.972) with significant value was 0.013 < 0.05 that showed simultaneously the effect toward students’ academic flow. The effective contribution to achievement motivation and social support for academic flow was 11.1%, while the remaining 88.9% is the contribution of not examined variables in this research. Thus, the experience of flow in academic activity needs to be improved to do online learning process optimally.